Coupled Lithospheric Deformation in the Qinling Orogen, Central China: Insights From Seismic Reflection and Surface‐Wave Tomography - Zhang, Yueqiao; Dong, Shuwen; Wang, Haiyan; Feng, Mei; Thybo, H.; Li, Jianhua; Gao, Rui; Shi, Wei (Geophysical research letters, 2022)
We combine a ∼485 km‐long seismic reflection profile and a S‐wave speed transect from surface‐wave tomography, to reveal the lithospheric deformation mode of the intracontinental Qinling orogeny, central China. We observe a thick lithosphere keel in the convergence zone between the Yangtze Block and the North China Craton (NCC) and a shallow‐crustal (8–15 km depth) décollement that extends into the lower crust of the Qinling Orogen. Combining with surface structural geology and magmatism, we interpret these seismic findings as kinematically linked features formed by renewed intracontinental convergence between the NCC and the Yangtze Block in the late Mesozoic. We highlight that the ∼40 km lithospheric thickening in the convergence zone was likely balanced by > 130 km thin‐skinned crustal shortening along a crustal‐scale strain‐transfer décollement, and was responsible for the occurrence of late Mesozoic magmatism (∼160–100 Ma) at the southern edge of the NCC. Plain Language Summary Here we reveal the lithospheric deformation mode of the intracontinental Qinling orogeny, central China, through a seismic reflection profile and a S‐wave speed transect from surface‐wave tomography. Our results suggest a thick lithosphere keel in the convergence zone between the Yangtze Block and the North China Craton (NCC), and a shallow‐crustal (8–15 km depth) décollement that extends into the lower crust of the Qinling Orogen. Coupled with published surface data, we suggest that these seismic findings document the lithospheric deformation induced by late Mesozoic intracontinental convergence between the NCC and the Yangtze Block. It appears that the ∼40 km lithospheric thickening was balanced by >130 km thin‐skinned crustal shortening along a long‐distance strain‐transfer décollement. Key Points We reveal the lithospheric deformation mode of the intracontinental Qinling orogeny, central China The ∼40 km lithospheric thickening was likely balanced by >130 km thin‐skinned crustal shortening The long‐distance strain‐transfer décollement plays a vital role in accommodating the crustal shortening and lithospheric thickening